The Palgrave Handbook of Literary Memory Studies
XVIII, 571 p. 2 illus.
Keywords: This handbook offers a comprehensive overview of the connections between memory and literature. Organized into six interrelated sections, the book explores both the value of approaches and concepts from literary studies for memory scholarship and the plurality of ways in which literature can advance theories of memory. Chapters cover reading and writing memory and literature; remediations and intersections; local and global cultures; postcolonial and decolonial approaches; environmental and more-than-human memory and literature; and law and justice. It offers an indispensable resource for students and scholars of both literary and memory studies. Lucy Bond is a Reader in Literature and Memory Studies at the University of Westminster, UK. She has published widely on the culture and politics of memory and trauma. Her work includes Frames of Memory After 9/11: Culture, Criticism, Politics and Law and the New Critical Idiom guide to Trauma (co-authored with Stef Craps). Lucy has also published edited collections including: The Transcultural Turn: Interrogating Memory Between and Beyond Borders; Memory Unbound: Tracing the Dynamics of Memory Studies; and Planetary Memory in Contemporary American Fiction. Susannah Radstone is Honorary Principal Fellow in the University of Melbourne's School of Culture and Communication, Australia. She co-edited the path-breaking Routledge series ‘Studies in Memory and Narrative’ and convened the long-running London ‘Cultural Memory’ seminar. She co-organised, (with Katharine Hodgkin and Stan Papoulias), the first major international Memory Studies conference (‘Frontiers of Memory’, Institute of Education, 1999). Publications include The Sexual Politics of Time and Memory and Methodology and co-edited volumes including Regimes of Memory; Contested Pasts; Culture and the Unconscious; and Public Emotions. She is currently researching memories of film festival-going and writing a book of her own memory work. Jessica Rapson is a Senior Lecturer in Culture, Media and Creative Industries at King’s College London, UK. She has published widely on commemorative environments and difficult heritage including the monograph Topographies of Suffering: Buchenwald, Babi Yar, Lidice. She is also the co-editor of The Transcultural Turn: Interrogating Memory Between and Beyond Borders and Planetary Memory in Contemporary American Fiction. She is currently researching, with Lucy Bond, the British Academy/Leverhulme Trust sponsored project Processing Memory: Heritage, Industry and Environmental Racism in the American Gulf States.